Intertidal rocky shore fauna and flora of Quintana Roo, Mexico. - González-Solis, Alicia (2015)
Rocky shores of limestone origin are common ecosystems in the state of Quintana Roo in Mexico. In the summer of 2012, a field investigation of rocky intertidal communities was performed in 10 sites in the state, both in the Riviera Maya and the Grand Costa Maya in order to know if there are any patterns in the abundance and diversity groups that compose them. In each site, three perpendicular transects were evaluated; transects had a variable number of levels, depending on the length of the beach. For each level, a sample of 25 cm2 was obtained, making a total of 593 samples. The slopes of the beaches were variable (0.4-1 m); however, as a recurring pattern, the Southern part of each beach was more extense than the Northern part. The fauna was represented by the following groups: echinoderms (15 species-11 genera), mollusks (84-50), annelids (10-9), crustaceans (23-22), sipunculids (1-1) chordates (1-1), algae (53-34), establishing a total of 187 species belonging to 128 genera. The results showed that mollusks dominated in all tidal flats; other groups were mostly found towards low intertidal areas. Regional geographical patterns of abundance, richness and biodiversity were unclear for some groups. The site with the highest richness and diversity was Osho Oasis in the Riviera Maya. Sites assemblages to a level of similarity of 50 %, had strong bonds between sites of the Riviera Maya and Costa Maya interchangeably, except echinoderms, identified and adjusted to that level of similarity among both areas. Using a monotetic content information analysis of order 2, with the aim to obtain the species responsible for the largest declines of information from each group, we have obtained the following results: Algae-Padina santae-crucis, Mollusks-Tectarius antonii, Crustacean-Maera inaequipes, Echinoderms Tripneutes ventricosus and Annelida-Pseudonereis variegata, these species are considered indicative of changes in community structure of each group and could be subject of further investigations to support management programs in the area.